The Role of Sponsorship and Mentorship in Overcoming Racial Barriers to Healthcare Leadership for African Americans (International Journal of Scientific Research and Management (IJSRM), 2025)
Despite increasing focus on diversity in healthcare leadership, African Americans remain significantly underrepresented in executive positions. This mixed-methods study investigated how sponsorship and mentorship influence African Americans’ advancement into healthcare leadership roles, with particular attention to overcoming systemic racial barriers. Through semi-structured interviews (n=24) and validated questionnaires, we examined the lived experiences of African American healthcare professionals who successfully navigated advancement barriers. Statistical analysis of questionnaire data and phenomenological analysis of interview transcripts revealed that while mentorship provided valuable guidance, sponsorship emerged as the critical factor in achieving executive positions (p < .001). Key themes included the differential impact of sponsorship versus mentorship (Cohen’s d = 0.82), the role of social capital in career advancement, and strategies for overcoming institutional barriers. These findings suggest that healthcare organizations should prioritize formal sponsorship programs alongside existing mentorship initiatives to create sustainable pathways for African American leadership advancement. To improve African American representation, organizations should implement structured sponsorship programs that include clear objectives, accountability measures, and training for sponsors to effectively advocate for their protégés.